PERANAN DEWAN PERWAKILAN RAKYAT DAERAH PROVINSI RIAU DALAM FORMULASI KEBIJAKAN DI PROVINSI RIAU TAHUN 2015 - Monalisa, Monalisa; Ibad, Irsyadul (UIR PRESS, 2018)
The role of the Riau Provincial People's Legislative Council in the Formulation of Policies in Riau Province is the role undertaken by the Riau Provincial DPRD in the Formation of Riau Provincial Regulations covering Stages of Planning, Drafting and Discussion referring to applicable normative rules, including: Law Number 12 Year 2011 Concerning the Establishment of Laws and Regulations, Law Number 23 Year 2014 concerning Regional Government, as well as Riau Province People's Legislative Decree Number 30 of 2014 on the Procedures of the Provincial People's Representative Council of Riau Province. The object of this research is the draft of Local Regulation on Ulayat Land and Its Utilization. Policy formulation is an integral part of the process of Establishment of Regional Regulation because it involves the process of collecting and articulating the Interest, the process of policy discussion in the DPRD Riau Province, and finally gave birth to a policy product in the form of Local Regulation. The results of the study authors is that the normative, the role of Riau Provincial DPRD in the formulation of local regulations running quite well, because it has followed the mechanisms and procedures that apply. However, in terms of policy formulation, the authors see that the policy output, in this case the Regional Regulation on Ulayat Land and Its Utilization has not been implemented because policy input, in the form of Academic Paper is not so profound, so it has not got a rigid picture about the existence of Ulayat Land and Society Customary Law whose existence still exists and is recognized to date, and at the discussion stage is also less involving public participation actively and deeply, so that the material substance regulated in the Regional Regulation can not be implemented until now.